2007
DOI: 10.1128/cvi.00274-06
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of High-Affinity Human Monoclonal Antibodies to Human Immunodeficiency Virus Type 1 Envelope Glycoproteins in a Mouse Model Expressing Human Immunoglobulins

Abstract: Human (Hu) monoclonal antibodies (MAbs) against the human immunodeficiency virus type 1 (HIV-1) envelope glycoproteins (Env) are useful tools in the structural and functional analysis of Env, are under development both as potential prophylaxis and as therapy for established HIV-1 infection, and have crucial roles in guiding the design of preventative vaccines. Despite representing more than 50% of infections globally, no MAbs have been generated in any species against C clade HIV-1 Env. To generate HuMAbs to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Previously, it has been reported that immunisation of transgenic mice with purified HIV-1 envelope protein alone (HIV-1 CN54 rgp140) derived from CHO cells resulted in isolation of very few cell lines and 2 clones (Sheppard et al, 2007). By contrast, this study demonstrates that priming with the DNA expression plasmid used to transfect CHO cells and express the HIV-1 envelope protein employed for the immune boosting yielded a higher frequency of hybridoma cell lines expressing anti-clade C HIV-1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that immunisation of transgenic mice with purified HIV-1 envelope protein alone (HIV-1 CN54 rgp140) derived from CHO cells resulted in isolation of very few cell lines and 2 clones (Sheppard et al, 2007). By contrast, this study demonstrates that priming with the DNA expression plasmid used to transfect CHO cells and express the HIV-1 envelope protein employed for the immune boosting yielded a higher frequency of hybridoma cell lines expressing anti-clade C HIV-1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies (Abs), mAbs and other reagents were obtained from the same sources as previously described60, with the exception of: CD4-IgG251 manufactured by Progenics Inc. and obtained from The International AIDS Vaccine Inititative Neutralizing Antibody Consortium Repository; CD4-binding site (CD4bs)-specific mAbs 15e and 21h obtained from the National Institute of Health (NIH) AIDS Research and Reference Reagent Program; the rabbit antiserum to gp120, ARP421 obtained from the Centralised Facility for AIDS Reagents (CFAR, NIBSC, Potters Bar, UK. Donated by S, S. Ranjbar); D7324, the goat polyclonal Ab (pAb) to the gp120-C-terminal region, from Aalto Bio Reagents Ltd (Dublin, Ireland); human mAbs HJ16 (CD4bs), HR10 (V3) and HG68 (V2) from D. Corti and A. Lanzavecchia54.…”
Section: Methodsmentioning
confidence: 99%
“…ELISAs were performed as described previously60 except the plates were washed six times following the addition of antisera or mAbs and after the addition of the anti-species IgG HRP conjugates. The absorbance of pre-immune serum was subtracted from that of the post vaccine bleeds before calculation of the endpoint titre by interpolation of the point of intersect between the assay cut-off and a sigmoid dose-response curve fitted to the dilution series in GraphPad Prism v5.061.…”
Section: Methodsmentioning
confidence: 99%
“…75,76 Recently, we have successfully isolated several cross-reactive high-affinity nonneutralizing mAbs by panning a phage-displayed library constructed from an acutely infected patient (W. Chen et al, unpublished work). These antibodies target gp41, one of which significantly competes with a cross-reactive neutralizing antibody, m44, 70 in binding to gp140s.…”
Section: Hiv-1 Monoclonal Antibodiesmentioning
confidence: 99%
“…74 Instead of eliminating the virus, these antibodies facilitate its production in the body of infected persons by different means including antagonizing neutralizing antibodies. The reported [75][76][77] and more ''bad'' antibodies that are to be identified could be used as reagents to further characterize the neutralizing antibodies of interest.…”
Section: Development Of New Approaches To Isolate More Potent and Bromentioning
confidence: 99%